Music therapy & autism : social interaction, nonverbal communicative behaviours and emotional responses in a group music therapy setting - Galanaki, Angeliki (2020)
The effects of Music Therapy on clients diagnosed with Autism Spectrum Disorder have been examined in several studies. There is evidence that music therapy has a positive impact on autistic people’s social skills, communication and interaction. Not all researches agree on this point, though. In this study, video excerpts from 16 music therapy sessions were analyzed. The video data refer to a group with a 4-years old boy with autism, two typically developed children and two music therapists. The aims of this study is to describe the changes observed in the social interaction and nonverbal communicative behaviours of a child with ASD as well as to examine his emotional responses in a group music therapy setting. The findings suggest that in those video excerpts there is an increase in the social interaction and communicative behaviours as well as that the child with autism responds with positive emotions to the music therapy process.